Decoding in-cell respiratory enzyme dynamics by label-free in situ electrochemistry - Yoshihide Tokunou; Tomohiko Yamazaki; Takashi Fujikawa; Akihiro Okamoto (Proceedings of the National Academy of Sciences, 2025)
Deciphering metabolic enzyme catalysis in living cells remains a formidable challenge due to the limitations of in vivo assays, which focus on enzymes isolated from respiration. This study introduces an innovative whole-cell electrochemical assay to reveal the Michaelis–Menten landscape of respiratory enzymes amid complex molecular interactions. We controlled the microbial current generation’s rate-limiting step, extracting in vivo kinetic parameters ( K m , K i , and k cat ) for the periplasmic nitrite (NrfA) and fumarate (FccA) reductases. Notably, while NrfA kinetics mirrored those of its purified form, FccA exhibited unique kinetic behavior. Further exploration using a mutant strain lacking CymA, a periplasmic hub protein, revealed its crucial role in modulating FccA’s kinetics, challenging the prevailing view that molecular crowding is the main cause of discrepancies between in vivo and in vitro enzyme kinetics. This platform offers a groundbreaking approach to studying cellular respiratory enzymatic kinetics, paving the way for future research in bioenergetics and medicine.